Effects of a nutraceutical supplement on gastrointestinal health in racing standardbreds. Issue 3 (6th March 2021) - Wellard, Leah; Medyk, Katryna; Pearson, Wendy
Abstract: Background: Feed additives that accelerate gastrointestinal transit time may help support normal gastrointestinal function in horses at risk for impaction colic. Previous research has demonstrated significant stimulatory effect of a hemp‐based nutraceutical product (Gs Formula; GF) on contractility of gastric smooth muscle and gastrin production in vitro . Objectives: To quantify effects of GF on indicators of GIT transit time and tight junction proteins. Study Design: Randomized placebo‐controlled cross‐over study. Methods: Eight Standardbreds were administered 200 plastic beads by nasogastric tube before (baseline; BL) and after receiving a diet containing GF (CON: 0 g/day, LO: 160 g/day or HI: 480 g/day) for 28 days. Total manure collection occurred every 2 hours for 72 hours after bead administration. Outcome measures included GIT transit time, faecal dry matter (DM), water intake, and complete biochemistry and haematology screens. Results: There was no effect of GF on GIT transit time. Faecal output was significantly lower in LO and HI horses than CON horses after 28 days on the supplement. HI horses have significantly lower rouleaux formation and lower faecal DM on Day 28 compared with BL. GF also produced changes in electrolytes associated with pH balance, which may indicate a role for GF as an alkalinizing compound in exercising horses. Clinical pathology results support the safety of GF up to 480 g/day for 28 days with no adverse effects being observed in haematology or biochemistry results. Main Limitations: Future studies on GF should focus on evaluating effect of GF on gastrointestinal transit in horses with naturally or experimentally delayed gastrointestinal motility, and its effect on exercise performance and onset of fatigue. Conclusions: GF may help support normal gastrointestinal function in horses at risk for impaction colic by reducing faecal DM and rouleaux formation.